Inconsistent definitions of GDP: Implications for estimates of decoupling - Gregor Semieniuk (University of Massachusetts, Department of Economics, 2022)
Efforts to assess the possibilities for decoupling economic growth from negative environmental impacts have examined their historical relationship, with varying and inconclusive results. Part of the problem is ambiguity about definitions of environmental impacts, e.g. whether to use territorial or consumption-based measures of environmental impact. This paper shows that ambiguities arising from definitional changes to GDP are sufficiently large to affect the outcomes. I review the history of structural revisions to GDP using the example of the United States, and on international comparisons of purchasing power parity, compare decoupling results using various historical definitions of GDP on the same environmental indicator, and demonstrate that changing the GDP data vintage does impact decoupling results in qualitatively important ways, with and without purchasing power parity. Inconsistencies in economic measurement introduce an additional layer of ambiguity into historical decoupling evidence and model projection into the future. To advance debate and be clear about scenario assumptions, rigorous reporting of GDP definitions used and the sharing of data vintage for subsequent comparison and replication are urgently needed.
Keywords: 330; decoupling; national accounting; GDP revisions; energy intensity; environmental Kuznets curve